2021
DOI: 10.4103/jmas.jmas_233_20
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after giant hiatus hernia repair

Abstract: Background: Elective surgery is the treatment of choice for symptomatic giant hiatus hernia (GHH), and quality of life (QoL) has become an important outcome measure following surgery. The aim of this study is to review the literature assessing QoL following repair of GHH. Methodology: A systematic literature search was performed by two reviewers independently to identify original studies evaluating QoL outcomes after GHH surgery. MeSH terms such as paraoesophageal; hiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
(184 reference statements)
1
0
0
Order By: Relevance
“…Of the 56 patients who underwent operative management, there were no mortalities, and four patients (7.1%) required a re-operation for recurrence demonstrating that GHH repair is a safe operation with low recurrence rates and excellent QoL improvement up to two years postoperation. This finding is consistent with Date et al's systematic review of QoL post-GHH repair [16]. The QOLRAD tool demonstrated significant improvements in all QoL domains.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 56 patients who underwent operative management, there were no mortalities, and four patients (7.1%) required a re-operation for recurrence demonstrating that GHH repair is a safe operation with low recurrence rates and excellent QoL improvement up to two years postoperation. This finding is consistent with Date et al's systematic review of QoL post-GHH repair [16]. The QOLRAD tool demonstrated significant improvements in all QoL domains.…”
Section: Discussionsupporting
confidence: 90%
“…Five out of these six studies reported no statistically significant differences between the two groups. 24 An important finding in our study was that prior to repair patients with large hiatus hernias had significantly worse quality of life outcomes than the general population of that age group (>65 years), and after surgery the physical and mental component scores and subscales scores returned to levels similar to the general population, confirming the significant benefit of laparoscopic repair of large hiatus hernia.…”
Section: Pre-operative Versus Longer-term Follow-up Scores P-valuesupporting
confidence: 69%